STAFF NEWS. (Historic New Orleans Collection Quarterly)
The article announces staff updates on The Historic New Orleans Collection (THNOC) as of April 2020, including Kacell Hmaidan as computer client services technician, the retirement of staff member Betty Killeen, and a two-session panel moderated by reference associate Robert Ticknor and professor Beth Manley.